Leveraging local assets: Empowering Langsa’s community through mushroom cultivation on palm oil waste - Sari, Juli Dwina Puspita; Chalil, Rifyal Dahlawy; Safarida, Nanda; Midesia, Shelly (PERDIKAN (Journal of Community Engagement), 2025)
Langsa City, a significant palm oil producer in Aceh Province, generates approximately 724,185 tons of waste annually, with empty fruit bunches (EFB) being the primary type of waste. This significant amount of by-side product coexists with a persistent regional poverty rate (10.23%), creating a critical challenge but also a unique opportunity. This article addresses the issue of unexploited economic potential and unemployment by examining the potential of EFB waste as a valuable resource for community empowerment. The initiative applied the Asset-Based Community Development (ABCD) model through a community service program titled “The Langsa Local Community Mushroom Project.” The method involved three key stages: 1) an initial survey to assess community needs, 2) stakeholder socialization to build commitment, and 3) a comprehensive workshop for 40 participants. The workshop provided theoretical and practical training in cultivating mushrooms using EFB as the primary growth medium, utilizing a local waste asset directly. The program yielded significant outcomes. Pre- and post-test assessments revealed a dramatic 37-point increase in participant knowledge, with average scores rising from 45% to 82%. This research demonstrated a successful transfer of skills. Furthermore, the project yielded tangible results, including a functioning community mushroom cultivation site, and fostered a clear behavioral change. Hence, the initiative confirms that the ABCD model is highly effective in transforming a local waste problem into an economic opportunity.[Kota Langsa, sebagai penghasil kelapa sawit utama di Provinsi Aceh, menghasilkan limbah sekitar 724.185 ton per tahun, dengan Tandan Kosong Kelapa Sawit (TKKS) sebagai limbah utama. Kelimpahan produk sampingan ini beriringan dengan tingginya angka kemiskinan daerah (10,23%), yang menciptakan tantangan kritis sekaligus peluang unik. Artikel ini membahas masalah potensi ekonomi yang belum dimanfaatkan dan pengangguran dengan mengeksplorasi penggunaan alternatif limbah TKKS menjadi sumber daya berharga untuk pemberdayaan masyarakat. Inisiatif ini menerapkan model Asset-Based Community Development (ABCD) melalui program pengabdian masyarakat berjudul “Projek Jamur untuk Komunitas Lokal Langsa.” Metode yang dilakukan melibatkan tiga tahap utama: 1) survei awal untuk menilai kebutuhan masyarakat, 2) sosialisasi kepada pemangku kepentingan untuk membangun komitmen, dan 3) workshop komprehensif bagi 40 peserta. Workshop ini memberikan pelatihan teoritis dan praktik mengenai budi daya jamur dengan menggunakan TKKS sebagai media tumbuh utama, yang secara langsung memanfaatkan aset limbah lokal. Program ini menghasilkan luaran yang signifikan. Hasil pre-test dan post-test menunjukkan peningkatan pengetahuan peserta yang signifikan sebesar 37 poin, dengan nilai rata-rata yang naik dari 45% menjadi 82%. Hal ini menunjukkan keberhasilan diadopsinya keterampilan yang baru. Lebih lanjut, proyek ini menghasilkan luaran berupa lokasi budi daya jamur komunitas yang berfungsi dan mendorong perubahan perilaku yang nyata. Dengan demikian, program ini menegaskan bahwa model ABCD sangat efektif dalam mengubah masalah limbah lokal menjadi peluang ekonomi.]